Grain quality of durum wheat varieties - Abugalieva A.I.; Morgounov A.Y. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Fourteen commercial varieties of durum wheat bred in Kazakhstan and Siberia along with Barilla Italy varieties from Kostanay, Akmola, North Kazakhstan, Aktobe and Karaganda regions were analyzed for test weight, ash, protein content, gluten quality, carotene and amylose content, vitreousness, ratios of gliadin and glutenin. The regions differed in mean values of the traits. The region of Aktobe was characterized by high protein content (by maximizing gliadin fraction) with the best gluten quality, with the maximum ratio of gliadin/glutenin and ash content. In Kostanay region vitreouss grain was formed with a relatively high carotene content and in Karaganda region the highest amylose content. Ranking of varieties based on integrated assessment of 11 traits in 4 regions resulted in the following order: Kargala 29 (1.983) >Zhemchuzhina Sibirii (2.002) >Altaiskaya Niva (2.158) >Kustanaiskaya 12 (2.270) >Damsinskaya yantarnaya(2. 308).
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)